2013
DOI: 10.1021/es401789x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Nitro-PAHs from the Heterogeneous Reaction of Ambient Particle-Bound PAHs with N2O5/NO3/NO2

Abstract: Reactions of ambient particles collected from four sites within the Los Angeles, CA air basin and Beijing, China with a mixture of N2O5, NO2, and NO3 radicals were studied in an environmental chamber at ambient pressure and temperature. Exposures in the chamber system resulted in the degradation of particle-bound PAHs and formation of molecular weight (mw) 247 nitropyrenes (NPYs) and nitrofluoranthenes (NFLs), mw 273 nitrotriphenylenes (NTPs), nitrobenz[a]anthracenes (NBaAs), and nitrochrysene (NCHR), and mw 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
95
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(106 citation statements)
references
References 53 publications
9
95
0
1
Order By: Relevance
“…They have been studied because of their carcinogenic properties (de Oliveira Seinfeld and Pandis, 2006). The nitrated and oxygenated PAHs (nitroand oxy-PAHs) are emitted as primary species or are formed in situ as secondary compounds (Kojima et al, 2010;Souza et al, 2014b;Zhou and Wenger, 2013;Zimmermann et al, 2013). They are potentially more mutagenic and/or carcinogenic than their PAH precursors (Franco et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They have been studied because of their carcinogenic properties (de Oliveira Seinfeld and Pandis, 2006). The nitrated and oxygenated PAHs (nitroand oxy-PAHs) are emitted as primary species or are formed in situ as secondary compounds (Kojima et al, 2010;Souza et al, 2014b;Zhou and Wenger, 2013;Zimmermann et al, 2013). They are potentially more mutagenic and/or carcinogenic than their PAH precursors (Franco et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1, 24,35,43 Additionally, this experimental result was also consistent with the observation reported by Zimmermann et al 24 They found that under actual ambient conditions where N 2 O 5 /NO 3 /NO 2 was present, very little possible formation of 1-NPY occurred in comparison with 2-NFL formation. 27 Thereby, we concluded that only small amount of 1-NPY may be formed through the heterogeneous processing of PY with atmospheric oxidants in the real atmosphere. Besides 1-NPY, 2-NPY, and a trace amount of 4-NPY were also observed in the heterogeneous reaction of PY under low humidity (0.5% RH).…”
Section: ■ Experimental Methodsmentioning
confidence: 77%
“…3-NFL and 1-NPY observed in the atmosphere possibly originate from primary emissions or heterogeneous reactions. In addition, because of the different reaction processes, the heterogeneous reactions of FL and PY with N 2 O 5 /NO 3 /NO 2 are quite different from the gas-phase reactions under atmospheric conditions, which produces 3-, 8-, 7-, 1-NFL, and 1-NPY as the major particulate nitration products [21]. However, 2-NFL is considered as the dominant particle-bound NPAH measured in ambient atmospheres, which possibly originates mainly from the gas-phase NO 3 reaction and condensation on the aerosol surface.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the rate constants of the NO 3 -initiated reaction (in the order of 10 −17 cm 3 molecule −1 s −1 ) were considered to be close to those of the N 2 O 5 reaction. More recent studies [12,21] have also suggested that 2-NFL and 2-/4-NPY are generated from the gasphase NO 3 -initiated reactions of FL and PY, respectively. Hence, the experimental results of the products and kinetics of FL and PY in the reaction with N 2 O 5 /NO 3 /NO 2 , as well as the postulated reaction mechanisms of N 2 O 5 with PAHs, need to be further confirmed theoretically.…”
Section: Introductionmentioning
confidence: 98%